Dogs with Lens Subluxation: Managing Vitreous Wick-Like Syndrome after Phacoemulsification - Hwang, Jiyi; Jung, Jiseung; Park, Kyung-Mee (Acta Scientiae Veterinariae, 2024)
Background: Etiologies for lens luxation in dogs include congenital, primary, and secondary. When performing cataract surgery on dogs with lens subluxation, several complications can arise, making it imperative to explore strategies for their prevention. This case report is the 1st to describe zonular fiber and vitreous strand prolapse through the incision site, a vitreous wick-like syndrome in human, as a potential complication of phacoemulsification with lens subluxation in dogs. It also introduces methods to prevent this complication. The procedures were performed on 2 dogs with lens subluxation at the Veterinary Medical Teaching Hospital of the Chungbuk National University (CBNU), Republic of South Korea. Cases: Case 1. A 7-year-old Maltese dog that exhibited signs of discomfort on the 1st day after undergoing phacoemulsification. This discomfort was due to a single severed zonular fiber with a vitreal strand protruding from the unsutured 2nd incision site, which tightly constricted the iris. Consequently, on the following day, a revision surgical procedure was necessitated to remove and reposition the protruding zonular and vitreal fibers that were constricting the iris. This corrective surgery effectively alleviated the dog's pain. Case 2. A 8-year-old Yorkshire Terrier with a similar issue was observed during phacoemulsification near the 2nd incision port. A zonular fiber with a vitreal strand had detached and protruded into the anterior chamber. Prompt and proactive measures were taken to preempt potential complications. The zonular fiber and vitreous were meticulously trimmed and removed, and the 2nd incision port was securely sutured. Unlike in the case 1, this proactive approach successfully prevented any postoperative complications for the dog of case 2. During the surgery to correct lens subluxation in both patients, a capsular tension ring was applied. In the case 1, the vitreous wick-like syndrome induced significant pain and intraocular inflammation. However, by suturing the 2nd incision port and removing the vitreous-zonule complex, the surgical complications were minimized in the dog of case 2. Discussion: Common complications associated with phacoemulsification for cataracts include corneal edema, uveitis, elevated intraocular pressure (IOP), posterior capsule opacification, and retinal detachment. Additionally, there is a rare but significant risk of vitreous wick syndrome. This syndrome is typically reported in human cases where the vitreous prolapses into the anterior chamber through a microscopic wound, subsequently forming a vitreous wick on the extraocular surface. It is most reported following intracapsular cataract extraction, though there are rare instances after posterior capsulotomies, corneal relaxation incisions, and intravitreal injections. The presence of a vitreous wick facilitates potential intraocular infections from normal superficial ocular bacterial flora, which may include serious conditions such as endophthalmitis and iris incarceration and can cause significant pain. Based on this case report, we recommend that when a severed vitreous-zonule complex is encountered in the anterior chamber during surgery, it should be excised as thoroughly as possible by micro scissors or vitrectomy device, especially when it is located near the incision site. Additionally, we suggest suturing the incision area as a precautionary measure. Keywords: canine, lens subluxation, phacoemulsification, capsular tension ring, vitreous wick syndrome, intraocular surgery.